Implementation of the Independent Learning Curriculum in PPKn Learning at SMP Negeri 9 Gorontalo - Safitri Tangahu; Zulaecha Ngiu; Rasid Yunus (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the implementation of the Independent curriculum in PPKn learning at SMP Negeri 9 Gorontalo and identify what factors cause the implementation of the Independent curriculum to be not optimal. The Merdeka Curriculum is a form of educational transformation in Indonesia launched by the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) as part of the Merdeka Learning program. This curriculum is designed to provide more flexibility to educational units, teachers, and students in the learning process. The goal is to create learning that is more relevant, in-depth, and in accordance with the needs of the times. The results of this study show that the implementation of the Independent Curriculum has brought significant changes in the learning system, especially in the subject of Pancasila and Citizenship Education (PPKn). This curriculum emphasizes the flexibility of teachers in designing student-centered learning, with character strengthening, Pancasila values, and the application of contextual and interactive learning. Innovations such as the Pancasila Student Profile Strengthening Project (P5) and a differentiated learning approach are considered to be able to increase student engagement and motivation. However, the implementation of this curriculum has not been running optimally in various educational units. Various obstacles are still faced, such as limited understanding and training of teachers, difficulties in preparing assessments and lesson plans, and limited facilities and resources, especially in remote areas. In addition, differences in students' readiness and abilities also affect the effectiveness of project-based learning. This research underscores the importance of intensive teacher training, equitable access to educational resources, and consistent mentoring as the main strategies in overcoming implementation challenges. Thus, the Independent Curriculum can be applied effectively and evenly, so as to truly create learning that is on the side of students.